Information Needs, Information Seeking Behavior and Information Provision to Rural Farmers in Bogoro Local Government Area, Bauchi State, of Nigeria - Makinta, Yusuf; Yakubu, William (European Journal of Applied Sciences, 2023)
This study examined information needs, information behavior and information sources of rural farmers in Bogoro Local Government Area of Bauchi State. The study was gadded by four (4) objectives and four (4) research questions. A survey research design was used for the study with one hundred and twenty two (122) populations drawn from farmers association groups (FGAs). The instrument used included questionnaire, interview and observation. Data collected was analyzed used descriptive statistics of frequency counts and percentages. The findings revealed that rural farmers need more information on various aspects of farming activities. Majority of them do not seek information from governmental, non-governmental agencies and the media. They relied on traditional methods among others. Four recommendations were proffered.